Neem seed cake enhances the efficacy of the insect pathogenic fungus Metarhizium anisopliae for the control of black vine weevil, Otiorhynuchs sulcatus (Coleoptera: Curculionidae). - Tariq Butt (Biological Control, 2008)
Shah F. A., Gaffney, M., Ansari, M. A., Prasad, M. &. Butt, T. M. 2008 Neem seed cake enhances the efficacy of the insect pathogenic fungus Metarhizium anisopliae for the control of black vine weevil, Otiorhynuchs sulcatus (Coleoptera: Curculionidae). Biological Control 44: 111-115 IF 2008 – 1.8 DOI: 10.1016/j.biocorttrol.2007.09.009 PUBLISHED JANUARY 2008